Pengaruh Struktur Modal, Ukuran Perusahaan, Integrasi Vertikal, dan Intensitas Ekspor Terhadap Profitabilitas Dan Nilai Perusahaan Periode 2021-2024 - Aditya Gunadi; Budiana Gomulia; Amelia Setiawan (Universitas Muhammadiyah Tangerang, 2026)
The textile and textile products (TPT) industry is one of Indonesia’s strategic manufacturing sectors, yet its profitability and firm value have been challenged by increasing import competition, rising production costs, and global market uncertainty. This study examines the effect of capital structure, firm size, vertical integration, and export intensity on profitability and firm value of TPT companies listed on the Indonesia Stock Exchange during 2021-2024. A quantitative research design was employed using secondary data from annual financial statements, analyzed through Partial Least Squares (PLS). Profitability was measured by Gross Profit Margin (GPM), while firm value was measured by PRICE-TO-BOOK Value (PBV). The findings reveal that capital structure and vertical integration positively and significantly influence profitability, whereas firm size and export intensity have no significant effect. In addition, capital structure, firm size, and profitability positively affect firm value, while vertical integration and export intensity show no significant influence. This study contributes to the literature by providing empirical evidence on the determinants of profitability and firm value in Indonesia’s TPT industry and highlights profitability as a key mechanism linking financial decisions to firm value. The study offers practical insight for managers and investors in improving corporate financial performance and value.